Two cases of debulking surgery for lower limb diffuse plexiform neurofibroma with transcatheter arterial embolisation. (2019) - Kitano, Daiki; Osaki, Takeo; Nakasone, Mika; Nomura, Tadashi; Hashikawa, Kazunobu; Terashi, Hiroto
Highlights: Debulking surgery was performed for DPN in two NF1 patients. Preoperative TAE with gelatin particles to tumour feeder vessels was conducted. TAE delayed wound healing; debridement and wound closure were required. Motor function improvement was confirmed in both patients. Abstract: Introduction: Diffuse plexiform neurofibroma (DPN) in patients with neurofibromatosis type 1 (NF1) causes motility dysfunction in severe cases. Transcatheter arterial embolisation (TAE) is an effective haemorrhage control method in vascular tumour surgery. Presentation of case: We performed debulking surgery for DPN in the buttock and posterior thigh of two NF1 patients. Preoperative TAE with gelatine particles to tumour feeder vessels was conducted in both cases. Operative bleeding volumes were 500 and 4970 mL, respectively. In the latter case, the resection area extended to the upper poles of the buttocks, and the tumour invaded deeply into the surrounding tissues. Massive haemorrhage occurred, and internal iliac arterial balloon was inflated temporarily to further suppress the bleeding. Delayed wound healing due to TAE occurred; debridement and wound closure were required. Motor function improvement was confirmed in both patients. Discussion: Bleeding volumes varied because of highly developed collateral pathways and tumour invasiveness. As the upper pole of the buttock was perfused by the superior gluteal artery and its numerous collateral vessels, complete haemostasis was difficult despite adequate TAE. Because delineating the tumour border from the normal tissue was impossible due to the high tumour invasiveness, cutting into the hypervascular tumour was inevitable. As gelatine particles were absorbed but remained within the vessels, prolonged wound ischaemia and delayed healing occurred. Conclusion: Although TAE with gelatine particles and balloon occlusion were reliable haemorrhage control methods in debulking surgery for lower limb DPN, optimal haemorrhage control technique, compatible with haemostasis and wound healing, was desired.